Herramientas de Conocimiento y Aprendizaje: Una Guía para Organizacion es Humanitarias y de Desarrollo - Ramalingam, Ben (ODI, 2006)
This toolkit presents entry points and references to the wide range of tools and methods that have been used to facilitate improved knowledg e and learning in the development and humanitarian sectors.
Keywords: spanish